IMPLEMENTASI KEBIJAKAN PEMBERIAN INSENTIF DAN KEMUDAHAN BERINVESTASI PADA SEKTOR INDUSTRI DI KABUPATEN KARAWANG - Khairunisa Rahmawati; Eka Yulyana; Lina Aryani (LPPM Universitas Abdurrab, 2026)
This study aims to analyze the implementation of policies on the provision of incentives and investment facilitation in the industrial sector of Karawang Regency. The main focus of this research is to assess the extent to which these policies have been effectively implemented based on Merilee S. Grindle’s theory of successful policy implementation (as cited in Subarsono, 2011), which encompasses two main dimensions: the content of policy and the context of implementation.This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews with informants from government institutions and industrial stakeholders, field observations, and documentation. Data analysis was conducted using a pattern-matching technique that compares empirical findings with theoretical patterns.The findings indicate that policies on investment incentives and facilitation in Karawang have a clear regulatory framework; however, their implementation has not yet been fully optimal. Several constraints were identified, including limited technical understanding of the OSS system among business actors, insufficient dissemination of information regarding investment incentives, unequal access to investment facilitation facilities, and inadequate supporting infrastructure in industrial areas. Nevertheless, the high level of investment realization demonstrates that Karawang remains a strategic destination for industrial development. Therefore, improvements in implementer capacity, infrastructure development, and periodic policy evaluation are required to ensure more effective and equitable implementation in the future.